Draft Annual Plan 1989-90 Government of Karnataka - Planning Commission (Planning Commission, 1988)
A little more than 21 percent of the expenditure is incurred under Social Services. The core sectors of Irrigation and Energy account for 42.7 percent of the total State Plan outlay. Among the Social Services, highest outlay goes for 'Water Supply, Housing & Urban Development'. 'Education' and 'Health' come next in importance.
Government of Karnataka, Planning Department